2002
DOI: 10.1034/j.1399-3054.2002.1160411.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of S‐adenosylmethionine synthetase genes and its expression is associated with ethylene synthesis in mustard (Brassica juncea)

Abstract: S-Adenosylmethionine synthetase (SAMS, EC 2.5.1.6) catalyses the conversion of methionine to S-adenosylmethionine, which is a precursor of ethylene biosynthesis. To investigate whether regulation of ethylene synthesis is associated with transcript accumulation of SAMS, we report the isolation and characterization of one mustard genomic clone (MSAMS2) and two cDNAs (MSAMS3, and MSAMS4) that are highly homologous to plant SAMS. While both MSAMS2 and MSAMS3 encoded a single polypeptide of 393 amino acid residues,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 38 publications
0
10
0
1
Order By: Relevance
“…A decrease in the endogenous SAM pool by expressing SAM hydrolase in a transgenic tomato line can lead to a reduction in ethylene production (Good et al, 1994). This further indicates that SAMS may play an important regulatory role in ethylene synthesis (Lim et al, 2002). It has been also observed that ACS and SPDS expression is altered by the overexpression or downregulation of SAMS (Kumar et al, 1997).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…A decrease in the endogenous SAM pool by expressing SAM hydrolase in a transgenic tomato line can lead to a reduction in ethylene production (Good et al, 1994). This further indicates that SAMS may play an important regulatory role in ethylene synthesis (Lim et al, 2002). It has been also observed that ACS and SPDS expression is altered by the overexpression or downregulation of SAMS (Kumar et al, 1997).…”
Section: Resultsmentioning
confidence: 94%
“…In previous studies, genes encoding SAMS have been cloned from several plant species including Arabidopsis thaliana (Peleman et al, 1989), parsley (Kawalleck et al, 1992), poplar (van Doorsselaere et al, 1993), rice (van Breusegem et al, 1994), tomato (Espartero et al, 1994), pea (Gómez-Gómez and Carrasco, 1996), kiwifruit (Whittaker et al, 1995), carnation (Larsen and Woodson, 1991), and mustard (Brassica juncea) (Wen et al, 1995). SAMS is also a ubiquitous enzyme and shows a high degree of conservation of ATP binding motif between eukaryotes and prokaryotes (Lim et al, 2002). The SAMS gene is strictly regulated by developmental and/or environmental factors (Boerjan et al, 1994) and is dependent on the tissue and organ type, the stage of growth, and the response to stress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…S-adenosylmethionine synthetases (SAM) may function to ethylene synthesis in mustard (Brassica juncea) (25). Curiously, a cluster of three ESTs (#33) encodes SAM.…”
Section: Est Analysis Implicated In Drought Stressmentioning
confidence: 99%
“…Sweetpotatoes were grown in a growth chamber at 25 C until further use. Quantitative RT-PCR was performed as described previously (35).…”
Section: Rt-pcrmentioning
confidence: 99%